2017
DOI: 10.1115/1.4035804
|View full text |Cite
|
Sign up to set email alerts
|

Detached-Eddy Simulation of Ground Effect on the Wake of a High-Speed Train

Abstract: The influence of ground effect on the wake of a high-speed train (HST) is investigated by an improved delayed detached-eddy simulation. Aerodynamic forces, the time-averaged and instantaneous flow structure of the wake are explored for both the stationary ground and the moving ground. It shows that the lift force of the trailing car is overestimated, and the fluctuation of the lift and side force is much greater under the stationary ground, especially for the side force. The coexistence of multiscale vortex st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is found that the CFL number remains below one, with only a small number of localized exceptions occurring. Previous studies have shown that this minor infringement on the stringent CFL requirement has no significant effect on the simulations [76][77][78]. The quality of the mesh has been checked by other quantities as well, such as the blending function and the turbulent viscosity ratio, which also confirm that the present mesh meets the requirement of the IDDES model [39].…”
Section: Mesh Independence and Numerical Validationsupporting
confidence: 72%
“…It is found that the CFL number remains below one, with only a small number of localized exceptions occurring. Previous studies have shown that this minor infringement on the stringent CFL requirement has no significant effect on the simulations [76][77][78]. The quality of the mesh has been checked by other quantities as well, such as the blending function and the turbulent viscosity ratio, which also confirm that the present mesh meets the requirement of the IDDES model [39].…”
Section: Mesh Independence and Numerical Validationsupporting
confidence: 72%
“…Bell et al 13,14 found that the flow field in the lower part of the train under flat ground condition differed significantly compared to embankment ground condition. Xia et al 15 found that the lateral force and lift force of the train fluctuated considerably, and the vortex pair shedding frequency was higher under the fixed ground through an IDDES simulation. Wang et al 16 used IDDES to investigate the effect of ground relative motion on slipstream under three different ground/wheel configurations.…”
Section: Introductionmentioning
confidence: 99%